Caracterização morfológica e funcional de vesículas extracelulares liberadas por células B-1 infectadas por Leishmania (Leishmania) Amazonensis - Toledo, Mayte dos Santos [UNIFESP] (2018)
Leishmaniasis is a group of diseases caused by protozoa belonging to the genus Leishmania. The immune response to leishmaniasis is complex and the outcome of the infection depends on several factors, such as genetic composition of Leishmania species and host immunity. Macrophages are known to play a central role in infection by Leishmania parasites and their activation may be influenced by several cell types, such as Th1, Th2, and B-1 lymphocytes. B-1 cells are a subtype of B lymphocytes with peculiar functions in immunity. These cells are able to produce regulatory cytokines (mainly IL-10), natural antibodies and differentiate into phagocytic cells. In addition to cytokines and antibodies, B cells can release different types of extracellular vesicles (EVs) with an important role in intercellular communication, with role in regulating activation and/or modulation of the immune system. However, the production of EVs by B-1 cells and their role in immunity have not yet been demonstrated The aims of this work were to characterize the EVs released by B-1 cells; to study the influence of these EVs on the modulation of lineage macrophages and medullary macrophages from different mouse strains; and to evaluate the role of EVs from B-1 cells in the course of experimental infection by L. (L.) amazonensis. Our results showed that EVs released by B-1 cells infected with the parasite led to a differential activation of J774A.1 macrophages, macrophages from BALB/c and C57BL/6 mice. In addition, EVs released spontaneously by B-1 cells led to a reduction in the lesion progression and parasite burden in BALB/c mice experimentally infected. Thus, this study demonstrated that B-1 cells can release EVs that are capable of altering the functions of macrophages in vitro. In vivo these EVs altered the course of L. (L.) amazonensis infection. This is the first evidence that EVs from B-1 cells can act as a new mechanism of cellular communication between macrophages and B-1 cells.